2009
DOI: 10.1176/appi.ps.60.3.384
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients With Depression at Heightened Risk of Suicide as They Begin to Recover?

Abstract: It has long been taught and believed that patients with depression and suicidal tendencies are at heightened risk of suicide as they begin to recover and their energy and motivation return. What are the data behind this enduring belief? More than a century ago, eminent clinicians noted that some patients with depression committed suicide just as their depression seemed to be improving. The clinicians went on to warn that early recovery carries a high risk of suicide. Although no studies have tracked suicide al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…7,10 However, a systematic review from 2009 showed that the research that has been carried out contradicts this belief, 21 and our review also suggests that it is wrong. We found that antidepressants double the risk of suicidality and violence, and it is particularly interesting that the volunteers in the studies we reviewed were healthy adults with no signs of a mental disorder.…”
Section: Discussionmentioning
confidence: 67%
“…7,10 However, a systematic review from 2009 showed that the research that has been carried out contradicts this belief, 21 and our review also suggests that it is wrong. We found that antidepressants double the risk of suicidality and violence, and it is particularly interesting that the volunteers in the studies we reviewed were healthy adults with no signs of a mental disorder.…”
Section: Discussionmentioning
confidence: 67%
“…Schweizer et al, 1988; Mittal et al, 2009), thus, when it is likely that someone has restored some psychic and physic resources, that may allow one to effectively deliberate, in contrast to those phases when one cannot even perform the simplest tasks of daily life. Moreover, one may doubt, whether this example really can account for an intact practical sense, albeit an “I can” is involved.…”
Section: The Depressive Situation – Changes Of Practical Sense and Mementioning
confidence: 99%
“…Furthermore, Mittal et al [7] claimed that improvement in depression may be accompanied by an increase in suicidal ideation. Few empirical studies are available regarding the temporal association between depression symptoms and suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…We define trajectories as longitudinal records of symptom severities that form progression patterns. Additionally, most available data regarding temporal associations between suicidal ideation and other symptoms of depression are derived from clinical trials rather than patients treated in community practices [79].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation